Evans syndrome and primary biliary cholangitis: A case report - Carranza-Castillo, Julio Enrique (2024)
In this report, we present the case of a patient diagnosed with Evans syndrome and primary biliary cholangitis, an unusual combination that to date has few cases reported in the literature. The patient presented complex clinical characteristics, which, based on epidemiological data, was first diagnosed as dengue with alarm signs due to positive IgG results for this infection; he presented with fever, jaundice with direct predominance of hyperbilirubinemia, anemia, alkaline phosphatase and persistent elevated gamma-glutamyl transpeptidase; for which additional laboratory and imaging tests were performed to consolidate the etiology of the symptoms presented, to finally be diagnosed with both conditions.